Dissociated and Reconstituted Cartilage Microparticles in Densified Collagen Induce Local hMSC Differentiation. (1st July 2016) - Novak, Tyler; Seelbinder, Benjamin; Twitchell, Celina M.; Voytik‐Harbin, Sherry L.; Neu, Corey P.
Abstract : Current use of decellularized articular cartilage as a regenerative platform suffers from limited implant diffusion characteristics and cellular infiltration. Attempts to address this concern using decellularized cartilage microparticles allow for customized implant shape, tailored porosity, and improved cell infiltration. However, these developments utilize severe crosslinking agents that adversely affect cell differentiation, and fail to attain clinically relevant mechanical properties required for the implant survival. These issues have been overcome through the formation of a composite approach, combining the advantages of mature, decellularized tissue with tunable features of a reconstituted collagen hydrogel system. Through the application of a plastic compression regime, cellularized composite structures are formed that exceeded the percolation threshold of the cartilage microparticles and exhibited clinically relevant mechanical properties. Chemical reduction and mechanical reconstitution methods to investigate the contributions of glycosaminoglycan and collagenous components to chondrogenic induction and matrix properties have been utilized. With the inclusion of human mesenchymal stem cells into the composite system, microenvironment‐dependent cell morphology and phenotype when in contact with cartilage microparticles are shown. This work demonstrates a cartilage microparticle composite matrix with clinically relevant mechanical properties, and chondrogenic differentiation of human mesenchymal stem that infiltrate both native and chemically reduced cartilage microparticles. Abstract : Decellularized cartilage microparticles, and all associated native signals, are delivered to human mesenchymal stem cell (hMSC) populations in a dense, type I collagen matrix. Hybrid usage of native tissue signals and the engineering control of collagen matrices show the ability to induce local infiltration and differentiation of hMSCs. Additionally, the solid cartilage microparticles inhibit bulk cell‐mediated contraction of the composite.